ANALISIS MAKNA UNSUR RUPA LOGO SYARIKAT DAGANG KAUMAN (SDK) SURAKARTA - Subhan Yuliyanto; Soegeng Toekio; Ahmad Khoirul (JURNAL KEMADHA, 2017)
The aim of this study is to determine how the design process, knowing aspect of consideration in the selection of the use of visual elements in the logo, and knowingthe meanings of what is contained on the visual elements of the SDK’s logo.The research method is descriptive qualitative research method. Based on the analysis ofdata obtained conclusions: (1) Visual elements contained in the logo are as follows: The line element in the logo . The non geometry shape element logo. The colorselements used in the logo. The texture element in the logo. (2) The meanings contained in the visual elements of the logo as expressed by the designer are as follows: Kepetform symbolizes a flower blooming. Logo color by Soga’s nature motif color. Typography of logo selected letters with the letter without hooks (sans serif) and italics